Magnetic flux leakage technique to detect loss in metallic area in external post-tensioning systems. (15th December 2019) - Karthik, Madhu M.; Terzioglu, Tevfik; Hurlebaus, Stefan; Hueste, Mary Beth; Weischedel, Herbert; Stamm, Ronald
Highlights: MFL is efficient in detecting strand defects in external tendons in field conditions. 80% defects with loss in metallic area (LMA) > 5% was consistently identified. Inspection data largely did not show any false-positive indications. Magnitude of LMA provides good indication of the severity of the defect. Abstract: Post-tensioned girders with internal and external tendons are widely used for the construction of bridges because of their eminent advantages. However, owing to poor grout quality, damage to protective ducts, exposure to environmental conditions, overstressing of strands, and overloading of the girder, the external tendons are susceptible to corrosion and breakage of strands. It is important to identify loss in cross-sectional area of the strands, in order to take preventive actions to avoid loss in capacity, and in some cases even failure of the tendon. Magnetic Flux Leakage (MFL), a non-destructive evaluation technique, is used to detect and quantify metallic defects in external post-tensioning systems. In order to evaluate this technique in in-service bridges under field conditions, a full-scale post-tensioned girder specimen was constructed as a control specimen. Metal defects that include section loss, corrosion, and breakage in wire and single or multiple strands with known loss in cross-sectional area, were fabricated and placed in the external tendons. The MFL device is then used to evaluate loss in metallic area (LMA) in the control girder specimen. The MFL device consistently detects LMA greater than 5% of the total strand cross-sectional area for the group of strands in a tendon. The measurements are found to be repeatable and reproducible. Even though there are errors associated with the estimated LMA percentages, especially for defects with greater than 50% loss in cross-sectional area, the estimated magnitude of the loss in total strand cross-sectional area gives a good indication about the severity of the defect.